SERS-based immunoassay for monitoring cortisol-related disorders - Villa, Javier E.L. [UNESP]; Garcia, Isabel; Jimenez de Aberasturi, Dorleta; Pavlov, Valeri; Sotomayor, Maria D.P.T. [UNESP]; Liz-Marzán, Luis M. (Elsevier, 2020)
As a natural response to a stressful situation, the human body produces cortisol. For this reason, cortisol is also called “the stress hormone” and is considered to be the principal stress biomarker. Although cortisol response to stress is essential for survival, abnormal levels in biological fluids may represent serious health risks. In this work, we present a cortisol biosensor which relies on a highly sensitive technique (surface-enhanced Raman spectroscopy, SERS) and a specific recognition (immunoassay). Gold nanostars were used as SERS nanotags, since they provided a better response than nanorods or nanospheres. Using the same concept, two different immunoassay modalities were evaluated, using either magnetic beads or gold-coated glass slides decorated with cortisol antibodies as the capture substrates. The magnetically-assisted SERS immunoassay presented a better performance and was therefore selected to quantify cortisol content in biological fluids (urine and serum). Significant advantages of this assay were found over standard methods such as Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS) and Enzyme-Linked Immunosorbent Assay (ELISA), including higher sensitivity and repeatability, minimum sample preparation, simplicity, and portability. Therefore, the proposed SERS immunoassay might be implemented as a highly efficient tool for in situ monitoring of human stress levels and cortisol-related disorders (e.g. Cushing's syndrome and Addison's disease).
Keywords: ELISA; Hydrocortisone; Magnetic separation; Plasmonics; Surface-enhanced Raman spectroscopy; UPLC-MS